Using a semantic wiki for technology forecast and technology monitoring. Issue 2 (4th April 2016) - Färber, Michael
Abstract : Purpose: – The purpose of this paper is to present extensions of Semantic MediaWiki for the purpose of technology forecast and technology monitoring. The user friendliness and applicability of the components is evaluated by task-based user studies. Design/methodology/approach: – Based on the requirements given by potential end users (technology experts), visualization possibilities were designed and implemented. Potential users used the new features of technology forecast and monitoring within a semantic wiki and were controlled regarding the effectiveness. Findings: – Although semantic wikis are ideal tools for knowledge management in industry settings, especially due to their user-friendly way of storing and retrieving knowledge, they have rarely been used for technology forecast and monitoring purposes so far. The authors show that the additional requirements for such purposes can be met and provide established technology analysis possibilities within Semantic MediaWiki. In that way, a new application area of Semantic MediaWiki is introduced. Originality/value: – Tools and techniques for Semantic MediaWiki are presented, opening the application area of Semantic MediaWiki for technology and innovation management. The research provides evidence that the open-source implemented visualization and storage techniques can be applied in real-world settings, where so far mainly costly dedicated software has had to be used.